Analysis of Different Data Analytics Tools (International Journal of Engineering and Computer Science, 2018)
Today a large number of data are being processed and new data are kept on increasing day by day. So there are a few different tools for analysis of the huge amount of data. The processing, modification, cleaning all is done with these tools. There are different tools for different process and method. Different tools are developed such as hive, Hbase, pig, flume, Oozie, and spark. These are used in the data analytics.Index Terms – Hive, Oozie, Hadoop, Data summarisation, Tools